On the Rationality of Fearing Death (Aporia, 2017)
If death by definition erases you, why should you fear it? For where you are, death will never be, and where death is, you will never be; it can never touch you. This intuition underlies Lucretius' famous argument that there is no reason to fear death. Taken seriously, it implies that you should be indifferent at the prospect of unexpectedly dying in your sleep tonight. To fear it would be to expect some experience that you will never undergo.In his paper The Makropulos case Bernard Williams develops the notion of "categorical desires" to refute this argument. In this paper, I will (I) explain Williams' argument that, contra Lucretius, we have reason to fear death; (II) raise, and subsequently amend, the objection that Williams' argument begs the question; and (III) argue that there is a response on Williams' behalf that blunts the force of the objection.